Convalescent plasma improves overall survival in patients with B-cell lymphoid malignancy and COVID-19: a longitudinal cohort and propensity score analysis - Hueso, Thomas; Godron, Anne-Sophie; Lanoy, Emilie; Pacanowski, Jérôme; Levi, Laura I.; Gras, Emmanuelle; Surgers, Laure; Guemriche, Amina; Meynard, Jean-Luc; Pirenne, France; Idri, Salim; Tiberghien, Pierre; et al. (Leukemia, 2022)
Patients with hematological malignancy and COVID-19 display a high mortality rate. In such patients, immunosuppression due to underlying disease and previous specific treatments impair humoral response, limiting viral clearance. Thus, COVID-19 convalescent plasma (CCP) therapy appears as a promising approach through the transfer of neutralizing antibodies specific to SARS-CoV-2. We report the effect of CCP in a cohort of 112 patients with hematological malignancy and COVID-19 and a propensity score analysis on subgroups of patients with B-cell lymphoid disease treated ( n = 81) or not ( n = 120) with CCP between May 1, 2020 and April 1, 2021. The overall survival of the whole cohort was 65% (95% CI = 56–74.9) and 77.5% (95% CI = 68.5–87.7) for patients with B-cell neoplasm. Prior anti-CD20 monoclonal antibody therapy was associated with better overall survival, whereas age, high blood pressure, and COVID-19 severity were associated with a poor outcome. After an inverse probability of treatment weighting approach, we observed in anti-CD20–exposed patients with B-cell lymphoid disease a decreased mortality of 63% (95% CI = 31–80) in the CCP-treated group compared to the CCP-untreated subgroup, confirmed in the other sensitivity analyses. Convalescent plasma may be beneficial in COVID-19 patients with B-cell neoplasm who are unable to mount a humoral immune response.